Study on Housing Practices Followed by Dairy Animal Owners in Anand District of Middle Gujarat Region - Patel, PA; Patel, YG; Modi, RJ; Trivedi, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present investigation was carried out to study dairy animal housing practices followed by dairy animal owners in the Anand district of middle Gujarat region. The data were collected from randomly selected 120 dairy animal owners interviewed personally with a well prepared questionnaire. The study revealed that all the respondents provided housing shelter with the all-time placement of their animals in the house. Majority of respondents (74.17%) constructed animal sheds nearby their own house followed by 25.83% were at a distance from farmer’s house. It was found that 64.17% of animal houses were oriented in east-west while 35.83% respondents had houses in a north-south orientation. The respondents provided pucca floor (63.33%) and galvanized iron sheets as a roofing material (49.17%) in their animal sheds, whereas 34.17% farmers had no provision of the wall in their animal sheds. The vast majority of respondents (85.00%) had the provision of good ventilation in their animal sheds and 72.50 % of the respondents had the provision of artificial light in their animal houses. Majority of dairy animal owners (72.50%) kept distance between manure pits and their animal sheds and 66.67 % respondents had provision and practice to protect animals from extreme weather. About 1/5th respondents used a curtain to reduce cold and very few owners (5.00%) provided bedding material to their animals. It was concluded that dairy animal owners of Anand district possess better knowledge regarding animal housing management and follow different practices of scientific animal husbandry.